2014
DOI: 10.3390/plants3030324
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Four Bifunctional Plant IAM/PAM-Amidohydrolases Capable of Contributing to Auxin Biosynthesis

Abstract: Amidases [EC 3.5.1.4] capable of converting indole-3-acetamide (IAM) into the major plant growth hormone indole-3-acetic acid (IAA) are assumed to be involved in auxin de novo biosynthesis. With the emerging amount of genomics data, it was possible to identify over forty proteins with substantial homology to the already characterized amidases from Arabidopsis and tobacco. The observed high conservation of amidase-like proteins throughout the plant kingdom may suggest an important role of theses enzymes in plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 71 publications
2
27
0
Order By: Relevance
“…PAA inhibited root elongation at 25 μM ( Figures 5A , 6A ), which is consistent with earlier reports on Arabidopsis (Sánchez-Parra et al, 2014; Sugawara et al, 2015). Bz-CN also led to reduced primary root length but the response was less severe than for PAA at equal concentrations ( Figures 1 , 5 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…PAA inhibited root elongation at 25 μM ( Figures 5A , 6A ), which is consistent with earlier reports on Arabidopsis (Sánchez-Parra et al, 2014; Sugawara et al, 2015). Bz-CN also led to reduced primary root length but the response was less severe than for PAA at equal concentrations ( Figures 1 , 5 ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, PAA is one of the few naturally occurring auxins and has been detected in several plant species, including Arabidopsis (Wightman and Lighty, 1982; Sauer et al, 2013; Sánchez-Parra et al, 2014; Sugawara et al, 2015). It was recently shown that PAA can be produced in vitro from phenyl pyruvate (PPA) by the activity of plant YUCCA (YUC) proteins and that the overexpression of YUC s led to increased PAA levels in Arabidopsis (Dai et al, 2013; Sugawara et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…4--Cl--IAA (Slovin et al 1999), and phenyl--2--acetic acid (PAA) . Moreover, a variety of IAA precursors such as indole--3--acetamide (IAM), indole--3--acetonitrile (IAN), indole--3--pyruvic acid (IPA), and indole--3--butyric acid (IBA) exhibit auxin--like effects, most likely due to their conversion to IAA (Sánchez--Parra et al 2014). However, these "other auxins" have commonly less pronounced effects than IAA (Abeles and Rubinstein 1964).…”
Section: Phytohormonesmentioning
confidence: 99%
“…In any case, a rising number of recent publications seem to valorise the importance of PAA in plants Sánchez--Parra et al 2014;Sugawara et al 2015;Westfall et al 2016). …”
Section: Importance Of Ami1 In the Plant Kingdommentioning
confidence: 99%
“…is also a naturally occurring auxin species that can be found widespread in plants (Sánchez-Parra et al 2014). Likewise, 2,4-dichlorophenoxyacetic acid (2,4-D) and 1-naphthaleneacetic acid (NAA), are two synthetic auxin derivatives with important economic value as herbicide or fruit growth enhancer, respectively (Bonner & Bandurski 1952;Ortolá et al 1991;Teale et al 2006).…”
Section: Auxin: An Overview Of Its Action and Regulatory Mechanismsmentioning
confidence: 99%